EasyEvac (2018)
"EasyEvac offers a simple, efficient and safe way to evacuate people that have a condition that limits their mobility, in emergency situations. Our team will ensure that the users will be included in the evacuation and that they will be able to complete the process successfully without risking their lives. EasyEvac is headquartered in Bogotá, Colombia. Our clients are people seeking for the well-being and safety of the population with reduced mobility, such as the Brigade staff that works under a facility, or the people with reduced mobility themselves. Furthermore, EasyEvac offers a variety of opportunities, including: safety, effectiveness, inclusiveness of the mobility reduced population, lessen the mortality rate of the mobility reduced population, low-Cost opportunity for developing countries. While we are currently a start-up, our solution is unique in the country. Although there are other devices that are currently used in the process of an evacuation, our solution offers a faster way to evacuate people with reduced mobility. Not only that, but our low-cost design is perfect for developing countries that do not have inclusive emergency protocols. EasyEvac primarily guarantees that the evacuation will be safe for the user, always seeking to reduce their stress and anguish during these situations. Our design is perfect because unlike other devices, it can be managed by the person itself or it can count with the assistance of a trained person."--Tomado del Formato de Documento de Grado